Assessment and Determination of Bittering Agents, Essential Oils, and Antioxidants of Gesho (Rhamnus prinoides L. Herit) Collected from Amhara Region, Ethiopia - Abebe Worku Negash; Belay Tilahun Tadesse; Berhanu Andualem Tsehai (Journal of Chemistry)
Rhamnus prinoides (Gesho) is an angiosperm dioecious plant, which is used for cash income, as a bittering agent for the preparation of the local alcoholic beverage and medicinal values. Although it has intense use, still its practical application is limited for local alcoholic beverage preparation, and there is no sufficient scientific report on the level and quantity of bittering agents, essential oils, and antioxidants of this plant. Therefore, the objective of this research was to assess and determine the bittering agents, essential oils, and antioxidants of R. prinoides. The leaves of R. prinoides were collected from eleven different sample sites and allowed to sun dry and then powdered. It was further dried in an oven at 60°C for 1 h, and then, total resin, essential oils, alpha acid, iso-alpha acid, beta acid, flavonoids, and polyphenols of R. prinoides were determined. All the data were analyzed using SPSS version 20.0. Based on this study finding, (16.03 ± 0.03–17.05 ± 0.04%) total resins, (10.00 ± 0.08–11.23 ± 0.07%) soft resins, (5.65 ± 0.11–6.40 ± 0.35%) hard resins, (1.82 ± 0.11–3.14 ± 0.02 mg/l) alpha acids, (2.26 ± 0.15–4.15 ± 0.10 mg/l) iso-alpha acids, (2.62 ± 0.04–4.29 ± 0.08 mg/l) beta acids, (7.74 ± 0.11–12.47 ± 0.13%) essential oils, (23.00 ± 0.14–25.01 ± 0.09%) flavonoids, and (2.11 ± 0.01–2.41 ± 0.02%) polyphenols were obtained in the leaves of R. prinoides. R. prinoides leaves taken from Tikledingay has shown statistically (P≤0.05) significant amount of soft resin (11.23 ± 0.07%), alpha acid (3.14 ± 0.02 mg/l), iso-alpha acid (4.15 ± 0.10 mg/l), essential oils (12.47 ± 0.13%), flavonoids (25.01 ± 0.09%), and polyphenols (2.41 ± 0.02%) in comparison with other samples. Generally, R. prinoides is a good source of bittering agents, essential oils, and antioxidants. However, the quantity of bittering agents, essential oils, and antioxidants in the leaves of R. prinoides was varied with sample collection sites. So R. prinoides can be used as a substitute for commercial hops used in the breweries, and promotion should be done to introduce the potential of Gesho as a bittering agent, source of aroma and flavor, and also antioxidant for beer and other alcoholic beverages.